Minangkabau Language as Ethnic Identity in Digital Era - Oktavianus, Oktavianus (Humanis; Vol 27 No 3 (2023)DO - 10.24843/JH.2023.v27.i03.p01, 2023)
This study aims to research Minangkabau language as an  ethnic identity in this digital era. The researcher did the study in five areas in West Sumatra. It is a qualitative study in which all language phenomena contributing to the validity of findings are considered. Data are collected through participative and nonparticipative observations. The data for this study are in the form of written and spoken language observed in the domain of families, public and cyberspaces. The researcher had discussions and interviews through participative observation. Taking notes and photos of written and printed Minangkabau language are done through nonparticipative observation. The researcher also observed Minangkabau language attitude through nonparticipative observation. The result of the study indicates that the productivity and creativity of using the Minangkabau language in family domains, public and cyberspaces strengthen the role of the Minangkabau language as an ethnic identity. Cultural setting and the needs to advertise local products are among the factors which trigger the use of the Minangkabau language as the symbol of Minangkabau identity.